1976
DOI: 10.1073/pnas.73.6.1839
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal proteins of Escherichia coli that stimulate stringent-factor-mediated pyrophosphoryl transfer in vitro.

Abstract: Guanosine tetra-and pentaphosphate, (p)pp~pp, can be synthesized in vitro in a reaction containing only the enzyme (stringent factor), salts, and substrates (nonribosomal system). This reaction is greatly stimulated upon addition of methanol (methanol system) or by ribosomes, mRNA, and tRNA (ribosome system). Here we show that several ribosomal proteins alone stimulate the synthesis of (p)ppGpp in the presence of stringent factor (protein system) The optimal ionic conditions for the ribosome and protein system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Finally, it should be noted that a class of (p)ppGpp synthesis-defective mutants exists, rel C (Parker et al, 1976) which has an altered ribosomal protein, LI 1. These mutant ribosomes can bind stringent factor (Christiansen & Nierhaus, 1976) but are unable to synthesize (p)ppGpp. It remains to be seen whether they are defective in binding tRNA or in the effector activity of the mutant ribosome-tRNA complex.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that a class of (p)ppGpp synthesis-defective mutants exists, rel C (Parker et al, 1976) which has an altered ribosomal protein, LI 1. These mutant ribosomes can bind stringent factor (Christiansen & Nierhaus, 1976) but are unable to synthesize (p)ppGpp. It remains to be seen whether they are defective in binding tRNA or in the effector activity of the mutant ribosome-tRNA complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent experiments suggest that normally only a few percent of the ribosomes have a bound RelA (153). The purified RelA enzyme cannot synthesize (p)ppGpp in the absence of ribosomes but can be activated by methanol, detergents, or specific proteins, suggesting that the activation signal in vivo is probably a ribosome-induced conformational change (43,253,318). relC mutations, which alter the gene for the large ribosomal subunit protein L11 (rplK), cause a relaxed phenotype both in vivo and in vitro, suggesting that wild-type L11 may relay the signal to RelA that uncharged tRNAs are present (84,246,262).…”
Section: Rela-(p)ppgpp Synthetase Imentioning
confidence: 97%
“…These results show that at the level of intact tRNA there is no special requirement for modified bases in the loop of tRNA in the synthesis of pppGpp. Nierhaus, 1976), and it has been reported that the entire tRNA molecule is not required, since the fragment TtFCG and larger oligonucleotides containing this fragment are weakly active in the presence of ribosomes and any mRNA-like polynucleotide (Richter et al, 1974;Erdmann et al, 1976). The unmodified version of T'PCG, UUCG, was inactive in this system, leading Erdmann and his colleagues to conclude that these two modifications serve as a specific recognition signal in tRNA for activation of stringent factor. This finding represents the first demonstration of any specific function for the ubiquitous TT^CG sequence, common to all elongator tRNAs as well as prokaryotic initiator tRNA (reviewed by Ofengand, 1977).…”
mentioning
confidence: 99%